A New Animal Model for Pathological Subcutaneous Fibrosis: Surgical Technique and in vitro Analysis - Marchesini, Andrea; De Francesco, Francesco; Mattioli-Belmonte, Monica; Zingaretti, Nicola; Riccio, Valentina; Orlando, Fiorenza; Zavan, Barbara; Riccio, Michele (Frontiers in Cell and Developmental Biology, 2020)
Fibrosis is a condition that affects the connective tissue in an organ or tissue in the restorative or responsive phase as a result of injury. The consequences of excessive fibrotic tissue growth may lead to various physiological complications of deformity and impairment due to hypertrophic scars, keloids and tendon adhesion without understating the psychological impact on the patient. However, no method accurately quantifies the rate and pattern of subcutaneous induced hypertrophic fibrosis. We, therefore, devised a rodent excisional model to evaluate the extent of fibrosis with talc. Tissue specimens were set on formalin, and paraffin sections for histological, immunohistochemical and molecular analysis talc was used to induce the fibroproliferative mechanism typical of hypertrophic scars. This pathway is relevant to the activation of inflammatory and fibrotic agents to stimulate human hypertrophic scarring. This model reproduces morpho-functional features of human hypertrophic scars to investigate scar formation and assess potential anti-scarring therapies.